Inovasi Biopori sebagai Langkah Strategis Membangun Desa Tangguh Bencana dan Meningkatkan Kualitas Lingkungan - Rohmat Hidayat; Anggi Indah Yuliana; Ambar Susanti; Sudarso Sudarso; Said Rian Al Hasan; Muhammad Aminuddin Ma’ruf; Sinta Ilmi Amaliyah; Umi Nur Azizah; Siti Sofia (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
Flooding due to stagnant water accumulation often occurs when rainfall exceeds the drainage system's capacity or when the soil cannot absorb water quickly enough. One effective solution to address this issue is to enhance the soil's infiltration capacity through biopore technology. By installing biopores, communities can significantly reduce surface water accumulation, especially after heavy rains. This community service initiative aims to raise awareness and promote active involvement in environmental care among residents. Additionally, the program focuses on educating the community about the benefits and techniques for creating biopore infiltration holes through social engagement. The approach taken is based on Asset-Based Community Development (ABCD), which prioritizes identifying and utilizing local community assets. The program consists of four main stages: familiarization, asset identification, planning, and implementation. These stages are structured to improve community self-sufficiency and well-being sustainably, engaging the villagers of Made as partners in the process. Overall, the initiative has led to positive outcomes regarding disaster preparedness and community welfare. It has successfully increased understanding of the importance of managing natural resources and the advantages of biopores. The active participation of community members in constructing biopores has resulted in a greater number of infiltration holes in residential areas and agricultural lands. To maintain the program’s sustainability, ongoing monitoring of the biopores and the availability of organic materials is crucial. Furthermore, replicating this initiative in other villages with similar challenges can broaden its positive effects on disaster readiness and community welfare.